PENGARUH PENERAPAN METODE PEMBELAJARAN RESITASI TERHADAP KEMAMPUAN SISWA DALAM MENULIS TEKS DEBAT KELAS X SMA NEGERI 1 LAWE BULAN - Sani Sani; James Marudut; Irfan Johari (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to determine the effect of the application of the Recitation Learning Method on Students' Ability in Writing Debate Texts for Class X SMA Negeri 1 Lawe Bulan in the 2021/2022 academic year. The method used in the quantitative approach. The research approach in this thesis uses a quantitative research approach. the population in this study were all students of class X SMA Negeri 1 Lawe Bulan in the 2021/2022 academic year, totaling 92 students consisting of 4 classes. The sample in this study was 21 students, namely class X IPS 1, which was taken using a purposive sampling technique or determined sampling. As for the results of the research and discussion that have been described in Chapter IV, it can be concluded that the Application of the Recitation Learning Method as a Debate Text Writing Learning for Class X Students of SMA Negeri 1 Lawe Month in the 2021/2022 Academic Year. This is evident from the average value of the initial test of Learning Writing Debate Text for students, which is 55.71 with a standard deviation of 9.95 and an increase in the final test score with an average value of 80.48 with a standard deviation of 7.85. the student and if it is associated with the Indonesian KKM score for high school is 75, then the Debate Text Writing Learning for the final test of students is included in good ability. In addition, at the observation t value > t table which is 9.00 > 2.08, then from the results of testing the hypothesis above, it can be concluded that there is an increase in the application of the Recitation Learning Method as an Effort for Learning to Write Debate Texts in Class X SMA Negeri 1 Lawe Months Years Learning 2021/2022